How does workplace event criticality spur employees’ proactivity? The roles of work engagement and mindfulness - Zhang, Yi; Gao, Lifang; Feng, Yuan (Frontiers in Psychology, 2022)
The purpose of this paper is to generate insights about whether, how and when workplace event criticality spur employee’s proactivity. We conducted multilevel analyses with a three-wave time-lagged survey of 179 employees and their 55 direct leaders in China to test our proposed model. The findings indicate workplace event criticality is conducive to stimulating employee proactive work behavior through improving employee work engagement. Further, employee mindfulness amplifies the positive relationship between workplace event criticality and work engagement. Despite the increasingly unavoidable influence of events in the workplace on employee proactivity, empirical research around their relationship and its underlying mechanism has been rather sparse. Our event-oriented research advances this knowledge unpacking the salient motivating role of workplace events criticality in employee work engagement and proactivity. It also increases our understanding by illustrating that employee mindfulness will act as an amplifier and intensify the motivational potential of workplace event criticality for work engagement.